Teaching Controversial Socio-Scientific Issues in Biology and Geology Classes: A Case Study - Reis, Pedro (2011)
Several educators in science have called for the inclusion of controversial socio-scientific issues’ discussion in science curricula because of its potential for creating a more real, humane image of scientific activity and for promoting scientific literacy, an essential tool for a responsible citizenship regarding decision-making processes related to socio-scientific issues. However, despite all the favourable opinions and empirical evidence concerning the educational potential for the discussion of socio-scientific issues, these activities are not part of many science lessons, even when the controversial socio-scientific issues comprise the curricular content and the teachers consider discussion of these issues important. This qualitative investigation, based on a case study centered on a Biology and Geology teacher, aimed to understand the factors that influence positively the conduction of discussion activities regarding controversial socio-scientific issues. By analysing data from interviews and class observations, it sought to understand the factors that motivate the teacher to implement this type of activity. This case study shows that the implementation of the discussion activities about controversial socio-scientific issues depends decisively on the teacher’s convictions about the educational relevance of these activities and the knowledge needed for their design, management and assessment. The development of these competences was triggered by professional development opportunities in which the teacher experienced new approaches under experts’ supervision.